Fluoxetine Inhibits Inflammatory Response and Bone Loss in a Rat Model of Ligature-Induced Periodontitis - Branco-de-Almeida, Luciana S.; Franco, Gilson C.; Castro, Myrella L.; dos Santos, Juliana G.; Anbinder, Ana Lia [UNESP]; Cortelli, Sheila C.; Kajiya, Mikihito; Kawai, Toshihisa; Rosalen, Pedro L. (Amer Acad Periodontology, 2012)
Background: Fluoxetine, a selective serotonin reuptake inhibitor, has been found recently to possess anti-inflammatory properties. The present study investigates the effects of fluoxetine on inflammatory tissue destruction in a rat model of ligature-induced periodontal disease.Methods: Thirty male Wistar rats were randomly assigned into three groups (n = 10 animals per group): 1) control rats (without ligature); 2) rats with ligature + placebo (saline; oral gavage); and 3) rats with ligature + fluoxetine (20 mg/kg/day in saline; oral gavage). Histologic analyses were performed on the furcation region and mesial aspect of mandibular first molars of rats sacrificed at 15 days after ligature-induced periodontal disease. Reverse transcription-polymerase chain reaction and zymography were performed to analyze the mRNA expression of interleukin (IL)-1 beta, cyclooxygenase (COX)-2, matrix metalloproteinase (MMP)-9 and inducible nitric oxide synthase and the MMP-9 activity, respectively, in gingival tissues samples.Results: Compared to the ligature + placebo group, alveolar bone loss was reduced in the fluoxetine group (P <0.05), and the amount of collagen fibers in the gingival tissue was maintained. Moreover, in gingival tissue sampled 3 days after ligature attachment, fluoxetine administration reduced IL-1 beta and COX-2 mRNA expression. Fluoxetine downregulated MMP-9 activity, without affecting MMP-9 mRNA expression induced by ligature, compared to the ligature + placebo group (P <0.05). These data suggest that fluoxetine suppressed proinflammatory responses, as well as proteolytic enzyme activity, induced by ligature.Conclusion: In the present study, fluoxetine suppresses the inflammatory response and protects against periodontal bone resorption and destruction of collagen fibers, suggesting that fluoxetine can constitute a promising therapeutic approach for periodontal diseases. J Periodontol 2012;83:664-671.
Keywords: Bone resorption; collagen; fluoxetine; inflammation; periodontitis